Att bearkadidh : Om samiskt självbestämmande och samisk självkonstituering - Nilsson, Ragnhild (Stockholms universitet, Statsvetenskapliga institutionen, 2021)
This thesis seeks to develop new ways to understand Sámi self-determination and self-constitution by analyzing Sámi understandings of these concepts and how such understandings, theoretically and politically, can challenge existing notions of what Sámi self-determination is, or can be in the future. According to the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP), indigenous peoples have the right to determine their own identity or membership in accordance with their own collective customs and traditions. They also have the right to participate in decision-making in matters which would affect their rights, through representatives chosen by themselves in accordance with their own procedures. The seemingly simple and obvious wordings in the UNDRIP, on the right of indigenous peoples to self-determination through their own procedures and their own political decision-making institutions give the impression that indigenous self-determination is something concretely formulable and directly implementable. In reality, UNDRIP presents a political dilemma regarding; 1. the extent to which it is possible for indigenous peoples to be able to formulate their own definitions of membership and the meaning of their own self-determination, free from the norms of the majority society; and 2. the extent to which it is possible to set up one's own procedures and institutions within the limits of what the nation state and liberal democracy allow. The study analyses the ideas the Sámi in Sweden have expressed about what Sámi self-determination is, how it can be implemented, i.e. what organisational solutions are proposed and what constitutes the group of Sámi that will exercise this self-determination. In addition to theory regarding indigenous peoples' legal and political right to self-determination, the thesis uses Sámi concepts (laahkoe, maadtoe, bearkadidh, dajve, maahtoe, vuekie) as an analytical framework to contrast existing legal/political theory and to capture Sámi norms and relational values ...